Investigation of the Effect of Irisin Hormone on the Viability of Hypothalamic Cell Lines - Ercan, Eda Coban; Keskin, Tuba; Ucer, Aysun; Canpolat, Sinan (Wiley, 2023)
[Abstract Not Available]
Keywords: GnIH; GnRH; Irisin; Kisspeptin; MTT; Olanzapine